Mendesain Antarmuka Pengguna Sistem Informasi Manajemen Aset TI menggunakan Pendekatan Desain Berpikir - Yogi Saputra; Agung Pratama; Nana Suryana; Popon Dauni; Novianti Indah Putri (JESII: Journal of Elektronik Sistem InformasI, 2026)
It is crucial to create an information system, especially for asset management, to design a good user interface (UI). The purpose of this study is to test the application of the Design Thinking method in the UI design process for the IT Asset Management Information System at PT Niaga Handal Cemerlang located in Bandung City. The Design Thinking method was chosen because of its user-focused approach, which allows for the creation of a functional and easy-to-use interface. Empathy, problem definition, ideation, prototyping, and testing are the steps in this study. This study found that applying Design Thinking can improve the quality of the user interface, which impacts how efficient the company's asset management is. These results support that a user-oriented approach is crucial when building complex information systems.